Conceptualizing and implementing the meaning of Africa's new partnership with the industrialized north : implications and possibilities for the renaissance - Somhlaba, Zamokwakhe Ludidi (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2005)
This study is a contribution to the on-going debate about the path that Africa has taken in realising the vision of its renewal. The central theme of the study is the idea of Africa's 'new partnership' with the industrialised North, which is envisaged under the New Partnership for Africa's Development (NEPAD). Acknowledging that asymmetrical partnerships have existed between Africa and the North, particularly in the last century, the question this study poses is: to what extent does the idea of the 'new partnership' represent something new? The study argues two points. Firstly, it argues that the idea of the new partnership has become a terrain of contestation between the Africanist and the post-modernist social forces. Secondly, the study argues that it is unlikely that conceptualising the idea of the new partnership in post-modernist terms will result in sustainable development and rebirth of Africa. That is particularly the case, because post-modernity suggests a certain degree of loyalty to the prevailing and asymmetrical global order. Against this background, the study concludes that the extent to which Africa will enjoy the benefits of a truly revised partnership with the North, and thus fulfil the vision of its rebirth, will be determined, by and large, by the modalities of accommodation and struggle between these social forces.
Keywords: New Partnership for Africa's Development; Sustainable development -- Africa; Economic development -- Africa; Africa -- Foreign economic relations; Africa -- Economic conditions -- 1960-